A brief report on the on-farm performance trial of genetically improved rohu - Yeasin, Mohammed (WorldFish, 2022)
WorldFish released genetically improved ‘generation 3’ or ‘G3’ rohu hatchlings to several hatcheries in Bangladesh in 2020-21 to be grown into broodstock. Subsequently, some hatcheries spawned the fish in mid-2022 for the first time and began selling the seed of this improved fish to nurseries and farmers. Over time, with more hatcheries spawning the fish and increasing broodstock biomass, G3 rohu seed is expected to be increasingly available in the market. In parallel to the release of G3 rohu hatchlings to hatcheries, WorldFish conducted an on-farm performance trial of the improved rohu strain at 19 semi-commercial farms in Jashore and Natore-Rajshahi regions from May 2021 to June 2022. The trial’s objective was to assess the growth performance of G3 rohu in comparison with two unimproved rohu strains – a control line, descended from fish collected from the Halda, Padma, and Jamuna rivers, and a well-regarded commercial strain, collected from a hatchery.